7(3y-2)-6y=

Simple and best practice solution for 7(3y-2)-6y= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(3y-2)-6y= equation:


Simplifying
7(3y + -2) + -6y = 0

Reorder the terms:
7(-2 + 3y) + -6y = 0
(-2 * 7 + 3y * 7) + -6y = 0
(-14 + 21y) + -6y = 0

Combine like terms: 21y + -6y = 15y
-14 + 15y = 0

Solving
-14 + 15y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '14' to each side of the equation.
-14 + 14 + 15y = 0 + 14

Combine like terms: -14 + 14 = 0
0 + 15y = 0 + 14
15y = 0 + 14

Combine like terms: 0 + 14 = 14
15y = 14

Divide each side by '15'.
y = 0.9333333333

Simplifying
y = 0.9333333333

See similar equations:

| 4x-5+9x+37=110 | | x^5z^4/xz^3 | | e^1/2x=2 | | 3x^4-2x^2+(-6x^5)-7x=0 | | 2x*2+4x=0 | | 4=35-X | | -6-2+(-5)=0 | | X-3+1=5x-4x+1 | | 7b-80=4 | | X-.12x=300000000 | | 30+2X=60 | | x+50=40 | | 258=29x | | x-6=3x+8 | | -75=X-41 | | x-21=5x+3 | | -30+X=-42 | | 5x+1+8x-8=t | | k-3/7k=-6/7 | | -2x+20=2x+8 | | x^2-12x^2+45=0 | | x^2-11x-11x+121=0 | | x^2+3-4=6 | | 1/6x+5/7x=111 | | 7+Y=23 | | Log(2x-14)+log(x-2)=2 | | (6x-18y+27z)-(3xyz)= | | 9x^2-4x=-3 | | x-6=5x+14 | | 8.5/x=7/5 | | -x-10=3x+18 | | x/17.5=7 |

Equations solver categories